Reflected sound: acoustic apprehension and ’resonant’ ontologies at Kurukop rock art site, Nama Karoo, South Africa - Rusch, Neil Graham (Southern African Humanities, 2024)
Kurukop is an archaeological site in the Nama Karoo drylands, South Africa. The metamorphic sandstone outcrop protrudes 23.6 m above the surrounding scrubland plain. The area (70 000 m2) is marked by petroglyphs (n = 112) and other signs of human presence, such as ostrich eggshell fragments and pottery, dating from c. 11 500 before present. Kurukop has an aural signature, with distinctive echo. Taking note of sound, an archaeoacoustic reading of the material remains and the engraved depictions is possible. It is hypothesised that site selection, archaeology and spatial transformation may include an acoustic dimension in a regionally specific ecology of sound. Recordings collected from an array of Impulse Response (IR) positions were subjected to spectrum analysis. The IR method has been applied in archaeoacoustic research at open-air and cave sites elsewhere in the world. At Kurukop there is an area of maximum echo intensity to the east and adjacent to two large rock pavements marked with engraved depictions. The archaeoacoustic data supports growing recognition of the sound sensibilities of indigenous people and their relational, ‘resonant’ ontologies, which in many cases pre-figure and intersect the domains of bioacoustic and ecoacoustic research.